Marketing strategies for internationalization in China’s higher education: an ally or barrier for sustainable development? - Zhou, Lei; Alam, Gazi Mahabubul; Mohd Rasdi, Roziah (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In this era of the commodification of higher education, the dominating concept of higher education now is that it functions as a commercial product for the purpose of national economic development. Consequently, the free market rules linked to consumerism seem to rule and shape how higher education should operate. A market-driven strategy may offer a benefit targeting the internationalization of higher education at the cost of sustainable development. This study investigates whether a commercialized strategy in the marketing of internationalized higher education helps or hinders sustainable progress in higher education. Adopting a qualitative method, this paper—the first of its kind in China—aims to obtain a comprehensive understanding of the rationales and current marketing strategies for international students. Here, the goal is to examine whether such strategies promote or hinder the development of sustainable education. The findings revealed that many internationalization marketing strategies may not survive well into the long term, and greater attention should be paid to enhancing the quality of international students and the quality of education they receive, as well as a sustainable higher education system. Institutions of higher education should rebrand themselves by enhancing the quality of what and how they teach, and cultivating competent international human resources.